2018
DOI: 10.1016/j.envres.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to residential green and blue spaces and anxiety and depression in adults: A cross-sectional study

Abstract: Our findings suggest a potential protective role of green spaces on mental health (depression and anxiety) in adults, but further studies, especially longitudinal studies, are needed to provide further evidence of these benefits and of the mediation role of exposures like air pollution and noise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
164
8
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(208 citation statements)
references
References 36 publications
12
164
8
3
Order By: Relevance
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…Another study was identified from the recent Internoise 2019 conference [52] giving a total of 34 studies for consideration. Ten studies were excluded as they did not directly measure noise [20,21,[24][25][26][27]35,37], or because no associations between noise exposure and mental health were reported in the paper [29,32] (see Appendix A.2). This left 24 studies for inclusion in the review.…”
Section: Grade Evaluationmentioning
confidence: 99%
“…NDVI was derived from six Sentinel 2 MultiSpectral Instrument (37) satellite images with a resolution of 10 by 10 m, obtained on 16 and 18 October 2017. In line with previous studies that analysed the effects of green space and blue space separately (17,23), we removed all water pixels from the satellite images with OpenStreetMap (OSM, OpenStreetMap Community, Cambridge, UK) water layer before determining NDVI. Mean NDVI values were extracted in circular buffers (or zones) within 100, 300, and 500-metre radius around participant's residence.…”
Section: Green Space and Blue Space Assessmentmentioning
confidence: 99%
“…The same mechanisms may apply to blue space (16,17). However, the evidence of the mechanisms underlying the effects of green/blue space is thin and sometimes conflicting (17)(18)(19)(20)(21)(22)(23). In addition, concerns have been voiced about the validity of the methods used to test these mechanisms.…”
mentioning
confidence: 99%
“…The neighborhood environment, as a mechanism for urban green spaces to bene t mental health, has been introduced (32-34). It has also been shown that access to green spaces over the long term potentially plays a protective role, bene ting mental health and alleviating anxiety and depression (35).…”
Section: Discussionmentioning
confidence: 99%